Peran QS Al-Ma’un dalam Membangun Kepedulian Masyarakat terhadap Pencegahan Penyakit Menular ISPA di Lingkungan Padat Penduduk Area Kota Depok - Suherman Jaksa; Irmawati Widyaningsih; Hanifah Nur Cahyaningsih; Aisyah Nur Hafida; Andriyani Andriyani; Nurmalia Lusida (LPP AIK UMJ, 2024)
Abstract. ISPA (Acute Respiratory Tract Infection) is an infection of the respiratory tract that can be transmitted through saliva, blood, sneezing, or airborne particles caused by microbes or bacteria. This has been observed in the illegal waste disposal site (TPA) in the Limo area, Cinere, Depok. Puspitasari (2024) reported that on August 27, 2024, residents in the Limo area protested and blocked access to garbage trucks, which led to an increase in ISPA cases. Purpose: This study aims to explore the role of QS. Al-Ma’un in fostering public awareness about the prevention of ISPA infectious diseases in densely populated areas in the Limo region, Cinere, Depok. Methods: Using a quantitative descriptive approach with a sampling technique based on the Simple Random Sampling method, this study was conducted because the exact population size is unknown. To determine the minimum sample size, the unknown population formula was applied, resulting in a total of 100 respondents. These respondents were residents affected by illegal landfill sites in the Limo area, Cinere, Depok City. Results: From 100 respondents who completed the questionnaire, the descriptive analysis results regarding the role of QS Al-Ma’un revealed that the highest sub-variable score was Concern and Concrete Actions in Preventing ISPA (Acute Respiratory Infections), with a total average score of 4.16, categorized as